Variable payment schemes and industrial relations: evidence from Germany. - Heywood, John S.; Hübler, Olaf; Jirjahn, Uwe (Kyklos, 1998)
The writers examine the empirical determinants of piece rates and profit sharing schemes. They analyze establishment data from Germany and contend that collective agreements make profit sharing less likely but that piece rates and profit sharing are more likely within the sector covered by collective agreements because of the presence of work councils. In addition, they contend that piece rates are made more likely in the uncovered sector by the use of teams.